1996
DOI: 10.1159/000264301
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Diagnosis of Upper Urinary Tract Dilation by Ultrasonography

Abstract: The criteria for the detection of fetal pyelectasis are still controversial. Prenatal and postnatal data from 2,170 consecutive pregnant women who underwent at least one antenatal ultrasound scan were prospectively studied. Fetal pyelectasis was defined on the basis of a mean renal pelvis dimension > 5 or 10 mm before or after 28 weeks of gestation, respectively. Pyelectasis was detected in 95 (4.4%) fetuses. Eighty-nine among them were explored after birth. In 13 (13.7%) cases, an obstructive urinary tract ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 19 publications
1
21
0
6
Order By: Relevance
“…We would like to have seen information on changes in fetal RP size during the pregnancy, but reporting was inconsistent, and some studies actually excluded fetuses in whom RPD resolved before birth, which biases their results toward worse outcomes (23,24,26 -28), and few mentioned details such as calyceal dilation, which has been reported to be useful indicators of poorer prognosis (8). Timing of initial postnatal ultrasound may also be critical as babies become relatively dehydrated and oliguric for the first 48 h postnatally (39), but several studies did not mention excluding measurements during this period (18,29,30,33). Differences in measurement and interpretation of outcomes also varied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We would like to have seen information on changes in fetal RP size during the pregnancy, but reporting was inconsistent, and some studies actually excluded fetuses in whom RPD resolved before birth, which biases their results toward worse outcomes (23,24,26 -28), and few mentioned details such as calyceal dilation, which has been reported to be useful indicators of poorer prognosis (8). Timing of initial postnatal ultrasound may also be critical as babies become relatively dehydrated and oliguric for the first 48 h postnatally (39), but several studies did not mention excluding measurements during this period (18,29,30,33). Differences in measurement and interpretation of outcomes also varied.…”
Section: Discussionmentioning
confidence: 99%
“…Five hundred and six potentially relevant studies were identified, of which 18 met the inclusion criteria (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Two studies reported overlapping patient cohorts but different outcomes (27,28).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These infants were of no increased risk for urinary tract infections and did not need further postnatal investigations. Langer et al [11] recommended the use of a mean value of renal pelvis dimension of not less than 10 mm beyond 28 weeks of gestation as threshold for detection of fetal upper urinary tract obstruction in the absence of ureteric and/or bladder dilatation. They suggested that values between 5 and 10 mm found in the second trimester of pregnancy should be confirmed by a repeat scan in the third trimester and that postnatal investigations should be limited to those with antenatal pyelectasis of 110 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The anteroposterior (AP) diameters of renal pelves were 6 mm in the right kidney and 6.2 mm in the left kidney. An AP pelvic diameter > 5 mm defines pyelectasis in the second trimester 2,3 . The parents opted to terminate the pregnancy.…”
Section: Second-trimester Sonographic Demonstration Of Retrognathia Amentioning
confidence: 99%